Proposed Marketing Strategy to Increase Number Of Customerstrough Experiential Marketing (Study Case: A Yoga Studio In Jakarta Selatan) - Ghassani Nabila Tanri; Nila Armelia Windasari (UniSadhuGuna Business School, 2023)
In May 2021, a new workout studio focusing on yoga classes officially launched. The yoga studio located in a very accessible area in South Jakarta. After a year of growing slowly, in the 3rd quarter of 2022 the studio faced a stagnancy on the number of customers. The studio’s marketing activites has only been focusing on its activation on social media specially Instagram which has successfully increased the followers number but failed to convert it into the studio’s customers by signing up for the classes. The studio then started to do some effort in another form by doing a special event collaborating with other brands resulting in new customers. The effort has shown the studio a high potential to acquire more customers, it also brought the studio to realize that the intangibility of their service can’t be promoted only through digital marketing. Based on this realization, a deeper reasearch then conducted to propose a new marketing strategy for the studio. Knowing the business issue of the studio, after analyzing the business situation, a root cause analysis then conducted using Current Reality Tree (CRT) resulting in 3 root causes. These root causes then led to some findings on the literature review and formed the conceptual framework which consisted in physical experience, servicescape, and brand collaboration that leads to customer’s experience resulting in patronage. Based on the findings, a online survey using questionnaire was conducted. The data proceeded using the multiple linear regression method by seeing the significance number then drawn into partial regression plot. After analyzing the result, the solution and implementation plan then formed.